268 Metastatic Ocular Melanoma to the Ovary Mimicking a Primary Ovarian Tumor, an Interesting and Rare Case Report. (11th January 2018) - Rubenstein, Wesley; Hasteh, Farnaz
Abstract: An abdominal CT scan from a 69-year-old woman showed multiple liver lesions favored to be metastasis from a previously diagnosed choroidal melanoma. Her past medical history is positive for enucleation for choroidal melanoma 19 years ago and a mastectomy for invasive ductal carcinoma 7 years ago. The CT scan also revealed an incidental solid ovarian mass. The patient underwent bilateral salpingo-oophorectomy where frozen sections showed a cellular spindle cell tumor where the main differential diagnosis included primary sex cord stromal tumor, especially cellular fibroma, vs metastatic melanoma. Permanent sections showed a cellular tumor with spindle to ovoid cells with scant cytoplasm arranged in intersecting bundles. Focally, some thick collagen bundles are noted in the background. Only rare mitosis is seen and no pigment is identified. Immunohistochemical staining revealed the tumor to be strongly positive for S100 and HMB45 with negative staining for calretinin, inhibin, SMA and desmin, confirming the diagnosis of metastatic melanoma. This case represents an exceptionally rare presentation of choroidal melanoma metastasizing to the ovary with only five previously reported cases in the medical literature. The most common site of metastasis for choroidal melanoma is the liver (90%), with foci of metastasis commonly disseminating to the lungs and pleura, skin, lymphatics and central nervous system. Other described sites of metastasis are very rare and include thyroid, adrenals, breast, ovary, uterus, and heart. In addition to the ovary being a rare site of metastasis, metastatic melanoma may present as a diagnostic challenge and is difficult to differentiate from an ovarian primary on frozen section. Immunohistochemical examination of S100, HMB45, MART-1, and SOX10 antibodies are crucial to reach a final diagnosis. Although metastasis of choroidal melanoma to the female genital tract is extremely rare, the possibility should not be ruled out even after a prolonged period without recurrent disease.